2019
DOI: 10.1021/acsbiomaterials.9b00967
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Disrupting Nanofibrous Peptide Hydrogels

Abstract: Self-assembled peptide nanofibers can form biomimetic hydrogels at physiological pH and ionic strength through noncovalent and reversible interactions. Inspired by natural antimicrobial peptides, we designed a class of cationic amphiphilic self-assembled peptides (CASPs) that self-assemble into thixotropic nanofibrous hydrogels. These constructs employ amphiphilicity and high terminal charge density to disrupt bacterial membranes. Here, we focus on three aspects of the self-assembly of these hydrogels: (a) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 107 publications
1
40
0
Order By: Relevance
“…Several studies have demonstrated the formation of antibacterial nanonets by amyloids, which inhibit the spread of microbes [ 176 , 177 ]. AMPs capable of forming hydrogels with mechanical protective properties for the further proliferation of both planktonic bacterial cells and biofilms are of particular interest [ 178 , 179 ]. Using the software AGGRESCAN [ 180 ], FoldAmyloid [ 181 ], PASTA 2.0 [ 182 ] and Waltz [ 183 ], we searched for and predicted amyloidogenic regions in a sample of 300 and 499 AMPs showing activity against Gram-negative and Gram-positive bacteria, respectively ( Figure 4 ).…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
“…Several studies have demonstrated the formation of antibacterial nanonets by amyloids, which inhibit the spread of microbes [ 176 , 177 ]. AMPs capable of forming hydrogels with mechanical protective properties for the further proliferation of both planktonic bacterial cells and biofilms are of particular interest [ 178 , 179 ]. Using the software AGGRESCAN [ 180 ], FoldAmyloid [ 181 ], PASTA 2.0 [ 182 ] and Waltz [ 183 ], we searched for and predicted amyloidogenic regions in a sample of 300 and 499 AMPs showing activity against Gram-negative and Gram-positive bacteria, respectively ( Figure 4 ).…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
“…Coil29 (QARILEADAEILRAYARILEAHAEILRAQ-NH 2 ) Ovalbumin 257-264 3B [121] PADRE (aKXVAAWTLKAa) 3B [121] PEPvIII (LEEKKGNYVVTDH) 3B [121] PEPvIII (LEEKKGNYVVTDH)/ PADRE (aKXVAAWTLKAa) 3B [121] Ovalbumin 323-339 3B [122] E214 (Ac-KFEGTEDAVETIIQAIEA) 3B [122] Ac-(Leu) 15 -Lys J8 (Ac-QAEDKVKQSREAKKQVEKALKQLEDKVQ)/ PADRE (AKFVAAWTLKAAA-NH 2 ) 3B [123] Ac-KKFKFEFEF Tyrosinase-related protein 2 180-188 3B [124] P10 (D[KIEKRIK] 5 KWWP) LSEIKGVIVHRLEGFFLLTRILTIPQSLD/gonadotropinreleasing hormone 3B [125] STQNAIDEITNKVN 3B [125] FF03 QVVHNSYNRPAYSPG 3B [126] AP205 SpyTag/Pfs25 3B [127] Mi3 SpyCatcher/cysteine-rich protective antigen 3B [128] SAPNs αTSR/ NANP/flagellin 3B [129] Matrix protein 2/HelixC 3B [130] P27/P27A 3B [131] Ac-AAVVLLLW Human papillomavirus E7 43-57 3B [132] Lumazine synthase nanoparticles Z-domain of protein A from Aquifex aelicus/ anti-HER2 antibodies/fluorescein 3B [133] AlDox (6-maleimidocapryl hydrazone) 3B [133] Sialic acid/Alexa Fluor 488 3F [134] Polyhedron protein from Autographa californica nucleopolyhedrovirus nanoparticles Open reading frame 2 from Porcine Circovirus Type 2 3B [135] NAVISQKKK-NH 2 KKK 3C [136] Ac-K 6 (SL) 6 K 6 -NH 2 Lysine residues 3C [137] Ac-WK x (QL) y K z -NH 2 Lysine residues 3C [138][139][140] Ac-WK 2 (QL) 6 K 2 -NH 2 /Ac-H 3 (QL) 6 Melittin 3C [141] K 3 W(QL) 6 K 2 -NH 2 Lysine residues/polyethylene glycol 3C [142] Fmoc-FFE Spermine 3C [143] Nap-FFE Spermine 3C [143] Nap-FFKK Lysine residues 3C [144] FFKK Naproxen 3C [145] Nap-FFFKK Lysine residues 3C …”
Section: Assembly Motif Display Motif Section Referencesmentioning
confidence: 99%
“…While activity against planktonic cells is important, the inhibition of multicellular bacterial biofilms is a particularly attractive goal for clinical biomaterials. Kumar and colleagues described a series of cationic and amphiphilic self-assembling, β-sheet forming peptides (CASP) that contain 2-8 lysine residues in their sequence to form hydrogels that could inhibit the formation of P. aeruginosa biolfims [132]. These sequences tolerated up to six lysine residues, with CASP-K8 not able to form gels at 20 mg/mL concentrations, leading to the team further validating the anti-biofilm activity of CASP-K6.…”
Section: Macroscopic Fibril Gelsmentioning
confidence: 99%